Beyond Boundaries: Ethnicity, Gender, and Class in Exod 1:8–2:10 - Peetz, Melanie 1977- (2025)
Exodus 2:1-10 has been thoroughly analyzed from a feminist perspective. This is appropriate because women play a significant role in the story. However, it is important to note that these female characters are not only defined by gender but also by ethnicity and social status. Combining analyses of ethnicity, gender, and class, this article demonstrates how the female figures in Exod 2:1-10 ignore, challenge, and subvert the polarizations established in Exod 1:8-22 by the Egyptian king. Exodus 2:1-10 can even be read as an example of cross-ethnic, cross-class, and cross-generational solidarity against a despotic regime that marginalizes and oppresses by using marks of differences. However, upon closer analysis it becomes evident that the female figures’ interactions are also determined by an unequal power dynamic. The article demonstrates how examining differences in gender, ethnicity, and class provides a nuanced understanding of power relations within biblical texts.
Keywords: Exodus; Hebrew Bible; Class; Ethnicity; female interaction; Gender; Oppression; Power relations; social categories